Brain volumes and cortical thickness on MRI in the Finnish Geriatric Intervention Study to Prevent Cognitive Impairment and Disability (FINGER) - Stephen R; Liu YW; Ngandu T; Antikainen R; Hulkkonen J; Koikkalainen J; Kemppainen N; Lotjonen J; Levalahti E; Parkkola R; Pippola P; Rinne J; et al. (BMC, 2022)
BackgroundThe Finnish Geriatric Intervention Study to Prevent Cognitive Impairment and Disability (FINGER) was a multicenter randomized controlled trial that reported beneficial effects on cognition for a 2-year multimodal intervention (diet, exercise, cognitive training, vascular risk monitoring) versus control (general health advice). This study reports exploratory analyses of brain MRI measures.MethodsFINGER targeted 1260 older individuals from the general Finnish population. Participants were 60-77years old, at increased risk for dementia but without dementia/substantial cognitive impairment. Brain MRI scans were available for 132 participants (68 intervention, 64 control) at baseline and 112 participants (59 intervention, 53 control) at 2years. MRI measures included regional brain volumes, cortical thickness, and white matter lesion (WML) volume. Cognition was assessed at baseline and 1- and 2-year visits using a comprehensive neuropsychological test battery. We investigated the (1) differences between the intervention and control groups in change in MRI outcomes (FreeSurfer 5.3) and (2) post hoc sub-group analyses of intervention effects on cognition in participants with more versus less pronounced structural brain changes at baseline (mixed-effects regression models, Stata 12).ResultsNo significant differences between the intervention and control groups were found on the changes in MRI measures. Beneficial intervention effects on processing speed were more pronounced in individuals with higher baseline cortical thickness in Alzheimer's disease signature areas (composite measure of entorhinal, inferior and middle temporal, and fusiform regions). The randomization groupxtimexcortical thickness interaction coefficient was 0.198 (p=0.021). A similar trend was observed for higher hippocampal volume (groupxtimexhippocampus volume interaction coefficient 0.1149, p=0.085).ConclusionsThe FINGER MRI exploratory sub-study did not show significant differences between the intervention and control groups on changes in regional brain volumes, regional cortical thicknesses, or WML volume after 2years in at-risk elderly without substantial impairment. The cognitive benefits on processing speed of the FINGER intervention may be more pronounced in individuals with fewer structural brain changes on MRI at baseline. This suggests that preventive strategies may be more effective if started early, before the occurrence of more pronounced structural brain changes.Trial registrationClinicalTrials.gov, NCT01041989. Registered January 5, 2010.